2011
DOI: 10.1007/s00221-011-2689-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of movement stability and congruency on the emergence of spontaneous interpersonal coordination

Abstract: The current project evaluated the relationship between the stability of intrapersonal coordination and the emergence of spontaneous interpersonal coordination. Participants were organized into pairs, and each participant was instructed to produce either an inphase or antiphase pattern of intrapersonal bimanual coordination using two hand-held pendulums, while simultaneously performing an interpersonal puzzle task. At issue was whether the emergence and stability of spontaneous interpersonal rhythmic coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
0
35
2
1
Order By: Relevance
“…Previous studies showed that inter-person coordination was stable when spatial relative phase was in-phase compared to anti-phase (Schmidt et al 1990(Schmidt et al , 1998Amazeen et al 1995;Temprado et al 2003;Temprado and Laurent 2004;Richardson et al 2008;Coey et al 2011), which is not in line with the present findings.…”
Section: Inter-personal Coordination Of Fingers and Toescontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that inter-person coordination was stable when spatial relative phase was in-phase compared to anti-phase (Schmidt et al 1990(Schmidt et al , 1998Amazeen et al 1995;Temprado et al 2003;Temprado and Laurent 2004;Richardson et al 2008;Coey et al 2011), which is not in line with the present findings.…”
Section: Inter-personal Coordination Of Fingers and Toescontrasting
confidence: 99%
“…Previous studies on inter-person coordination utilized movements including manipulating a pendulum (Amazeen et al 1995;Schmidt et al 1998;Richardson et al 2008;Coey et al 2011), manipulating a joystick (Temprado et al 2003;Temprado and Laurent 2004), knee flexion/extension (Schmidt et al 1990), and elbow flexion/extension for one subject with shoulder internal/ external rotation for the other (Kilner et al 2003;Fine et al 2013). Visual information derived from these inter-person coordination to form the coordination state was considered to be the spatial relative phase (Temprado et al 2003;Temprado and Laurent 2004;Fine et al 2013), and was thought not to be related to meaningful perceptual-cognitive behavior.…”
Section: Inter-personal Coordination Of Fingers and Toesmentioning
confidence: 99%
“…This isomorphism suggests again that coordination emerges from the dynamics of interaction rather than from the specific properties of the coordinated components. Such synergistic effects have also been observed in more ecological tasks such as martial arts and hand clapping games (Riley et al, 2011), rocking chairs (Richardson et al, 2007b; Frank and Richardson, 2010), in language games that imply turn-taking (Schmidt et al, 2011) or in problem-solving tasks (Shockley et al, 2003; Richardson et al, 2005; Coey et al, 2011; see also Richardson et al, 2008; Shockley et al, 2009; Fusaroli et al, 2014). During sport activities, whether players are opponents or not, the dynamics of their coupling spontaneously self-organize and attractors emerge from their collective dynamics as well (Bourbousson et al, 2008, 2010a,b; Travassos et al, 2011; Yokoyama and Yamamoto, 2011; Okumura et al, 2012; Duarte et al, 2013; García et al, 2013).…”
Section: Embodiment Of Intersubjective Timementioning
confidence: 79%
“…Using a similar paradigm, Coey, Varlet, Schmidt, and Richardson (2011) investigated unintentional interpersonal entrainment when each participant swung two pendulums in phase or in antiphase. Regardless of the participants' intrapersonal coordination mode, intermittent in-phase coordination occurred when the participants' coordination modes were congruent with each other, and to a lesser extent when they were incongruent.…”
Section: Unintentional or Spontaneous Entrainment 28mentioning
confidence: 99%